Efficacy of Intraperitoneal and Intravenous Chemotherapy for Advanced Gastric Cancer with Peritoneal Metastasis. Issue 5 (September 2014) - Chen, Yu; Wang, Xiao-Jie; Lin, Rong-Bo; Chen, Ling; Lin, Gen; Guo, Zeng-Qing
Aims and Background: Peritoneal metastasis (PM) in patients with advanced gastric cancer (AGC) is a poor prognostic indicator. The aim of this study was to compare the response of AGC patients with PM to paclitaxel-based systemic multidrug chemotherapy with and without additional intraperitoneal (IP) chemotherapy through retrospective analysis. Methods and Study Design: Two hundred and sixty-three AGC patients with PM were enrolled. Eighty-two patients received systemic paclitaxel/oxaliplatin and leucov-orin/5-fluorouracil (POF) and 181 patients received 2-drug systemic therapies, PO (paclitaxel + oxaliplatin) or PF (paclitaxel + 5-fluorouracil + leucovorin), and IP infusion of a third drug. Results: Patients who received the POF regimen had longer progression-free survival (PFS) and overall survival (OS) than patients who received PO/PF + IP therapy (P = 0.026 and P = 0.046), respectively. In subgroup analysis, no significant differences in PFS and OS were observed between the POF regimen and PF/PO + IP regimens in patients with isolated peritoneal metastatic disease. Patients with multiorgan metastatic disease receiving POF had better PFS and better OS than patients receiving PO/PF + IP chemotherapy (P = 0.005 and P = 0.036, respectively). In multivariate analysis, ECOG performance status and the interaction between different therapeutic strategies and multiorgan metastasis were independent prognostic factors for survival. Leukopenia, fatigue and peripheral neuropathy were higher on the triplet regimen than the doublet regimens. Conclusions: Paclitaxel-based doublet therapy combined with IP chemotherapy had more manageable toxicity and equal efficiency compared to triplet therapy for AGC patients with isolated PM. The POF regimen may be a good choice for AGC patients with multiorgan metastasis, especially those having a good performance status.